2014
DOI: 10.4028/www.scientific.net/amm.625.298
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Biomass-Derived Oxygen-Containing Intermediates into Chemical Raw Materials with Zeolite

Abstract: To establish a new production route of biomass-derived BTX and propylene, the catalytic conversion of oxygen-containing intermediates which are furfural, levulinic acid, acetic acid or butyric acid, obtained by hydrothermal reactions of bagasse or fermentation of molasses was investigated with zeolites, ZSM-5, SAPO-11 and SAPO-34. Levulinic acid and acetic acid were suitable for generating BTX with ZSM-5. On the other hand, the butyric acid was valuable for converting to chemical raw materials with ZSM-5. By u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Short-chain carboxylic acids (VFAs) can similarly undergo decarboxylation to produce light alkane or alkene gases that can be used as fuels or chemical feedstock. Goshima et al [1] reported the formation of propylene from butyric acid in the presence of zeolite catalysts. However, for energy application, C 1 -C 4 light alkanes are of commercial importance as clean-burning fuels (especially, methane, propane and butane in liquefied or compressed fuel gases) [21] or for the hydrogen production via steam reforming (methane) [22].…”
Section: R-ch 2 -Ch 2 -Cooh→r-ch 2 -Ch 3 + Comentioning
confidence: 99%
See 3 more Smart Citations
“…Short-chain carboxylic acids (VFAs) can similarly undergo decarboxylation to produce light alkane or alkene gases that can be used as fuels or chemical feedstock. Goshima et al [1] reported the formation of propylene from butyric acid in the presence of zeolite catalysts. However, for energy application, C 1 -C 4 light alkanes are of commercial importance as clean-burning fuels (especially, methane, propane and butane in liquefied or compressed fuel gases) [21] or for the hydrogen production via steam reforming (methane) [22].…”
Section: R-ch 2 -Ch 2 -Cooh→r-ch 2 -Ch 3 + Comentioning
confidence: 99%
“…There is a growing interest in the production of sustainable hydrocarbons from renewable bio-derived feedstocks (e.g., woody biomass, energy crops, vegetable oils, animal fats and other organic wastes and residues) for use as fuels and chemical feedstocks [1,2], proposed as a route to defossilisation of carbon-based chemicals and the energy sector. Essentially, the near-term target is to produce hydrocarbons from biomass that can be used as direct replacement for those derived from fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goshima et al (2014) stated that hydrothermal reactions of fermenting molasses or bagasse demonstrated the catalytic transformation of oxygen possessing biomass intermediates, such as butyric acid, acetic acid, levulinic acid, and furfural. Zeolites such as SAPO-34, SAPO-11, and ZSM-5 were examined to convert biomass derivatives propylene and BTX [ 115 ]. For generation of BTX with the aid of ZSM-5, acetic acid and levulinic acid were found to be appropriate.…”
Section: Potential and Challenges Of Zeolitementioning
confidence: 99%